Evoked temporal summation in dogs to assess pain central sensitization and modulation – A feasibility study - Aliénor Delsart; Maude Barbeau-Grégoire; Maxim Moreau; Colombe Otis; Aude Castel; Bertrand Lussier; Johanne Martel-Pelletier; Jean-Pierre Pelletier; Eric Troncy (PLoS ONE, 2026)
Central sensitization and pain endogenous controls imbalance were reported in humans affected by chronic pain. In cats, nociplastic changes, such as the wind-up phenomenon, ( i.e ., decreased tolerance to repeated stimuli) were described using a validated mechanical device inducing temporal summation of pain (TSP). The study aim was to validate this method in dogs and to describe pro- or anti-nociceptive profiles occurring with canine osteoarthritis (OA). Healthy ( N = 4) and OA ( N = 31) dogs were assessed. Six TSP stimulation protocols were tested for their reliability and specificity, at mid-antebrachium (0.38 Hz at 2–4Newtons [N], 0.25 Hz or 0.50 Hz at 4N) or tail-base (0.25 Hz or 0.50 Hz at 2N). Endogenous facilitatory, or inhibitory, controls were assessed using a pressure pain threshold (PPT) before and after TSP, or conditioning pain modulation (CPM) via an ischemic model, respectively. The PPT pre/post stimuli were used to calculate ratio of facilitation (< 0%) or functional inhibition (> 7%). Statistical analyses included intraclass coefficient of correlation, Spearman’s correlations, Fisher and Mann U tests, with α = 0.05. The response to mechanical TSP scores tended to be moderately reliable, while tail-base stimulation decreased inter-trials variability compared to mid-antebrachium for healthy dogs ( P = 0.029). The response was specific, OA dogs tolerated 50% less stimulations than healthy dogs at 0.5 Hz frequency and 2N ( P = 0.008). This protocol led to spinal hyperexcitability; among facilitated OA dogs, 45% presented functional inhibition versus 73% for the non-facilitated dogs. No correlations were found between radiographic score, orthopedic score, response to mechanical TSP or age with the facilitation or inhibition ratios ( P > 0.173). OA dogs developed central sensitization reflected by the wind-up phenomenon. An imbalance in favor of endogenous facilitatory controls was observed suggesting inhibitory control fatigue and neuroplasticity. Characterizing endogenous pain modulation will enable better management of OA pain by preserving inhibitory control and preventing its fatigue.